Variables Associated with the Phenomenon of Desertion of Students at the Fundación Universitaria Konrad Lorenz - Barrero, Johanna; Garzón, Gustavo; Gómez, Óscar (Pensando Psicología, 2013)
Advances in research into university desertion reveal multiple social, economic and academic causes, among others, of this phenomenon. However, the university population is heterogeneous and there are no defined profiles that can describe and accurately explain how each factor behaves. The Spadies system at the Colombian Ministry of National Education aims to analyze desertion rigorously; however, universities have to generate their own study processes. It is within this context that the Konrad Lorenz Foundation University is conducting this research, whose general objective is to identify the socio-demographic, financial and academic variables associated with student desertion at this higher education institution. This is an ex- post- facto retrospective single-group study. Its design is focused on reconstructing the events associated with student desertion at this institution among semester II of 2005, I and II of 2006 and I of 2007-II cohorts, by establishing possible relationships to sociodemographic, financial and academic variables. The population under study consists of a total of 846 undergraduate students from the abovementioned cohorts of the Systems Engineering, Mathematics, International Business Administration and Psychology programs. The results indicate that student desertion at this institution stems from academic reasons, particularly those associated with the cumulative grade average. This points to a predictive power for students who drop out, but not necessarily in relation to other socio-economic and socio- demographic variables. According to this study, the percentage of men who drop out is higher than that of women, even though more women enroll in the professional programs offered.